Design, Synthesis and Antifungal Activity of Novel 1-(Adamantan-1-yl) ethanone Oxime Esters - Liu, Si; Niu, Li-Zhi; Shi, Yan-Hua; Wan, Fu-Xian; Jiang, Lin (Letters in Drug Design & Discovery, 2020)
Background: Oxime compounds, including oxime ethers and oxime esters, possess various biological activities. Many oxime ethers have been widely used in the fields of pesticides and medicines. However, oxime ethers are rarely used in the field of pesticides. Methods: We chose the excellent fungicide pyrifenox as the lead compound, integrated pyridinyl, adamantyl and benzoyl moieties into one molecule, while also designed and synthesized ten 1- (adamantan-1-yl)ethanone oxime esters containing pyridinyl moiety. Moreover, we also evaluated their preliminary antifungal activities against S. sclerotiorum and B. cinerea. Results: The target compounds were characterized by NMR, IR and HRMS. The preliminary bioactivity test showed that they exhibited some antifungal activity to S. sclerotiorum and B. cinerea, and EC50 values were in the range of 14.16-32.97 and 27.60-52.82 μg/mL, respectively. Conclusion: Some target compounds such as 3d, 3e, 3h and 3i, exhibited moderate activities against S. sclerotiorum, with EC50 values of 14.16-18.18 μg/mL.
Keywords: pyridine